Ownership Structure and Financial Performance of the Technology Sector on the Indonesia Stock Exchange (2020–2024) - Apriani, Tari; Mukhzarudfa; Kusumastuti, Ratih; Tiswiyanti, Wiwik (Ridwan Institute, 2026)
This research aims to examine the effect of ownership structure on the financial performance of technology sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Ownership structure is proxied by institutional ownership, managerial ownership, and foreign ownership, while financial performance is measured using Tobin's Q as a market-based indicator of firm value. This study uses a causal-associative quantitative approach with panel data. The sample consists of 20 technology sector companies listed on the Indonesia Stock Exchange, selected through purposive sampling, resulting in 100 firm-year observations. Data drawn from annual reports, audited financial statements, and stock price records were analyzed using panel data regression with EViews 13. The results show that, simultaneously, institutional ownership, managerial ownership, and foreign ownership have a significant effect on the financial performance of technology sector companies. Partially, institutional ownership and managerial ownership have a positive and significant effect on Tobin's Q, indicating that stronger institutional monitoring and greater alignment of managerial interests contribute to higher firm value. In contrast, foreign ownership has a positive but statistically insignificant effect on financial performance. These findings indicate that domestic governance mechanisms, particularly institutional and managerial ownership, play a more important role in enhancing market valuation in the Indonesian technology sector during the post-pandemic and technology sector correction period. This study contributes to the corporate governance literature by providing evidence on the role of ownership structure in explaining firm value in a knowledge-based industry within an emerging market context.